Horseshoe kidney and uretero-pelvic-junction obstruction in a pediatric patient. Laparoscopic vascular hitch: A valid alternative to dismembered pyeloplasty? - Cosimo Bleve; Valeria Bucci; Maria Luisa Conighi; Francesco Battaglino; Lorenzo Costa; Lorella Fasoli; Elisa Zolpi; Salvatore Fabio Chiarenza (PAGEPress Publications, 2017)
Horseshoe kidney (HSK) is a congenital defect of the urinary tract that occurs in 0.25% of the general population. Laparoscopic Vascular Hitch (LVH) according to Hellstrom-Chapman represent an alternative approach in treatment of extrinsic hydronephrosis by crossing vessels (CV) in pediatric age. In our Department from 2006 to 2016, 36 children with extrinsic-Uretero-Pelvic-Junction (UPJ)-Obstruction (UPJO) underwent laparoscopic vessels transposition. Over the last 4years, we have treated three patients with extrinsic hydronephrosis in HSK; two males and one female respectively of 6, 7 and 8years. The side affected was the left in all patients; symptoms of onset: recurrent abdominal pain, vomiting with associated intermittent hydronephrosis at ultrasonography. The preoperative examinations performed were: ultrasound/Doppler scan, MAG3-renogram, functional-magnetic-resonance-urography (fMRU). Mean operative time was 120'; median hospital stay 3- days. Intraoperative diuretic-test (DT) confirmed an extrinsic-UPJO in all patients. No JJ-stents and drain were used and there were no perioperative complications. Clinical and ultrasound follow-up (18 months-4 years) show resolution of symptoms and decrease in hydronephrosis grade in all patients. Our series is the largest in pediatric population by a revision of the literature. We believe that LVH is feasible in patients with symptomatic hydronephrosis by CV in HSK. Intraoperative-DT and the correct selection of patients are crucial to the success of the technique. According to us, this procedure is appropriate in those cases where the UPJ-anatomy is disadvantageous to a resection/re-anastomosis between ureter and renal pelvis. Our initial results are encouraging, although long-term follow- up and a more significant patient sample are required.